2016
DOI: 10.3329/jafmc.v12i2.41079
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic Status of Drug Addicted Young People in Dhaka City

Abstract: Introduction: Drug addiction is a burning problem in Bangladesh affecting vast population especially the youths. The spread of multi drug use has aggravated the overall situation affecting our personal, economical and social life, impairing health status, increasing crime and other unwanted risky behaviour. Objective: To find out the socio-economical status of drug addicted young population in Dhaka City. Materials and Methods: This descriptive cross sectional study was performed during August 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…All information regarding study design, study population, data collection technique, instruments, data reliability, questionnaire etc. have been described elsewhere [ 22 ]. In our present study, we used BDHS-2014 data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All information regarding study design, study population, data collection technique, instruments, data reliability, questionnaire etc. have been described elsewhere [ 22 ]. In our present study, we used BDHS-2014 data.…”
Section: Methodsmentioning
confidence: 99%
“…None of these studies considered mothers’ BMI as a factor associated with duration of breastfeeding although some studies showed that BMI was significantly associated with breastfeeding status [ 19 , 20 ]. Household wealth quintile, women education level and medical facilities have been increasing in Bangladesh during the last decades [ 21 ], which may have effect on knowledge, attitude and practice on duration of breastfeeding [ 22 ]. Therefore, it is important to investigate the duration of breastfeeding among mothers in Bangladesh considering the latest nationally representative data.…”
Section: Introductionmentioning
confidence: 99%
“…More than 40% unemployed youth are addicted. And among addicted, more than 40% are female, close to 50% are educated and 60% are sex offenders, around 95% are smokers and more than 85% get into consuming drugs under the influence of friends [44][45][46][47][48].…”
Section: Prevalence Of Addiction In Bangladeshmentioning
confidence: 99%
“…Almost half of all drug use is in the capital, Dhaka (Gaffar and Deeba, 2017). While recent evidence demonstrates a relationship between unemployment and drug use (Rahman et al, 2016), patterns of substance abuse among urban adolescents and the social dynamics that lead to increased risk remain poorly understood (Islam, 2019).…”
Section: Box 64: Threats Facing Adolescents In Urban Spaces: Emerging...mentioning
confidence: 99%